2007
DOI: 10.1159/000102614
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to Paracetamol in Asian Children with Early Onset of Nonsteroidal Anti-Inflammatory Drug Allergy

Abstract: Background: The published incidence of paracetamol cross-reactivity in adults and adolescents with nonsteroidal anti-inflammatory drug (NSAID) reactions is low and all data on such reactions in young children is sparse. The study aim was to characterize the clinical presentation and cross-reactivity with paracetamol in patients with a reported onset of NSAID hypersensitivity before 6 years of age. Methods: A retrospective case review was done of patients with cross-reactive hypersensitivity reactions to antipy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
1
21
0
1
Order By: Relevance
“…We postulated that this was due to the adolescent's ability to communicate breathing discomfort and co-operate with a physical examination compared to the young child. Compared to the study by Rudders et al [12], our elicitors of adolescent anaphylaxis included a high proportion of shellfish anaphylaxis (13 vs. 5%) and NSAID drug anaphylaxis, reflecting the high incidence of locally published antipyretic drug allergy [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…We postulated that this was due to the adolescent's ability to communicate breathing discomfort and co-operate with a physical examination compared to the young child. Compared to the study by Rudders et al [12], our elicitors of adolescent anaphylaxis included a high proportion of shellfish anaphylaxis (13 vs. 5%) and NSAID drug anaphylaxis, reflecting the high incidence of locally published antipyretic drug allergy [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In one of the largest published series, there were slightly more cross‐intolerant patients than selective responders, but this was not the case in smaller studies . One important clinical feature is isolated facial angioedema especially localized on lips or eyelids, which seems to be more frequent in cross‐intolerants . In a study from Singapore, including atopic children, facial angioedema developed in all CI patients during OPTs, and in another one, including children younger than 6 years, it was the most common clinical manifestation, with a frequency of 83% .…”
Section: Epidemiology and Clinical Manifestations In Different Phenotmentioning
confidence: 97%
“…One important clinical feature is isolated facial angioedema especially localized on lips or eyelids, which seems to be more frequent in cross‐intolerants . In a study from Singapore, including atopic children, facial angioedema developed in all CI patients during OPTs, and in another one, including children younger than 6 years, it was the most common clinical manifestation, with a frequency of 83% . The incidence of NSAID‐induced facial angioedema was reported to increase with age in an atopic group of children and adolescents, being reported in less than 5% of infants and toddlers, but in up to 20% of adolescents and young adults .…”
Section: Epidemiology and Clinical Manifestations In Different Phenotmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst a recent Epinephrine auto-injectors prescription survey [4] showed that the most common food trigger is peanut allergy in children < 15 years old, the patients were mostly non-Singaporean children. In addition, non-food anaphylaxis cases in children have not been studied locally, but we have previously reported cross-reactive paracetamol and non-steroidal anti-inflammatory drug (NSAID) hypersensitivity amongst local children [5], and some complicated by anaphylaxis [6]. …”
Section: Introductionmentioning
confidence: 99%